The Influence of Career Development Through Certification and The Quality of Certification Implementation on The Performance of Polri Educator Members at The Republic of Indonesia Police Certification Institute - Switbertus Budhi Prasetiyo; Kemal Taufik; Sri Wahyuningsih (Dinasti Publisher, 2026)
The expected objectives of this study are to solve the following problems: To determine the effect of career development through certification on the work spirit of Polri educators, To determine the effect of the quality of certification implementation on the work spirit of Polri educators and To determine the effect of career development through certification (X1) and the quality of certification implementation simultaneously on work spirit. This is proven by the results of the partial test (t test) which shows a t-count value of 2.923 which is greater than the t-table of 1.995 at a significance level of 0.05, the quality of certification implementation has a positive and significant effect on the work spirit of Polri educators. The results of the partial test (t test) show a t-count value of 2.252 which is greater than the t-table of 1.995. Career development through certification and the quality of certification implementation simultaneously have a positive and significant effect on the work spirit of Polri educators. This is demonstrated by the results of the simultaneous test (F test), with an F-value of 13.988, which is greater than the F-table of 2.71, and a significance level of 0.000 < 0.05. Thus, the two independent variables jointly contribute significantly to improving the work morale of Polri educators. This is indicated by the coefficient of determination (R-square) of 0.233, meaning that 23.3% of the variation in work morale of Polri educators can be explained by these two variables, while the remaining 76.7% is influenced by other factors not examined in this study.